2021
DOI: 10.3390/antibiotics10070843
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prescribing in the Emergency Department; Who Is Calling the Shots?

Abstract: Objective: Inappropriate antimicrobial prescribing in the emergency department (ED) can lead to poor outcomes. It is unknown how often the prescribing clinician is guided by others, and whether prescriber factors affect appropriateness of prescribing. This study aims to describe decision making, confidence in, and appropriateness of antimicrobial prescribing in the ED. Methods: Descriptive study in two Australian EDs using both questionnaire and medical record review. Participants were clinicians who prescribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…In our study we observed a high rate of appropriate empirical antibiotic prescribing (94.4%). This rate is higher than in other published Australian studies, including 85% appropriateness in a Queensland ED, 28 and 75.7% appropriateness in the 2019 NAPS (involving 377 Australian hospitals). 29 We hypothesize this observed difference in our cohort compared with other published studies is due to the early involvement of EM pharmacists in the sepsis alert response and local ED sepsis guidelines including first-/second-/third-line options to guide empirical therapy in the presence of AALs.…”
Section: Discussioncontrasting
confidence: 57%
“…In our study we observed a high rate of appropriate empirical antibiotic prescribing (94.4%). This rate is higher than in other published Australian studies, including 85% appropriateness in a Queensland ED, 28 and 75.7% appropriateness in the 2019 NAPS (involving 377 Australian hospitals). 29 We hypothesize this observed difference in our cohort compared with other published studies is due to the early involvement of EM pharmacists in the sepsis alert response and local ED sepsis guidelines including first-/second-/third-line options to guide empirical therapy in the presence of AALs.…”
Section: Discussioncontrasting
confidence: 57%
“… 19 Antibiotic prescribing in the ED is complex and not every decision is guided by seniors or ID specialists. 20 Moreover, the analysed infectious diseases entities in this study are not typically surgical. The picture could be different for specific surgical diagnoses like appendicitis or cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Building on our previous research on challenges and potential improvements to antibiotic prescribing in EDs (Denny et al, 2019; Hamill et al, 2021), we sought to examine clinical communication around antibiotic treatment decisions as they unfolded at the point of care. Furthermore, as no prior studies used VRE to explore antibiotic prescribing practices, we assessed the acceptability of video-reflexive methods among clinicians working in a complex ED environment.…”
Section: Introductionmentioning
confidence: 99%